The State of the Fauna of Bats in the Ukrainian Azov Region in Modern Environmental Conditions - Volokh, Anatoly; Волох, Анатолій Михайлович; Gorlov, Petro; Siokhіn, Valery; Polishchuk, Іgor (Mykolaiv: PMBSNU – Rzeszow: RzUT, 2021)
ENT: The article presents the results of regional surveys of bats in 2010-2020 in places planned for the construction of wind farms. The almost complete transformation of the steppe into agrocenoses bordered by forest belts and irrigation canals undoubtedly affected bats against the background of global warming. With the use of modern ultrasonic detectors, licensed computer programs and an electronic library of voices, 15 species were found in the Ukrainian Pryazovia. Their greatest diversity (11–13 species) is recorded between the Dnieper valley and the Crimean Peninsula, where intensive migration flows take place. Probably, in this bottleneck, bats migrating from the northern and northeastern continental regions cross the land and join those moving along the Azov coast. During the winter, with limited research in this period, 8 species were identified, during spring and autumn migrations – 13 and in summer – 11 species. In recent years in the Ukrainian Pryazovia there has been a decrease in the number of Pipistrellus pygmaeus and Eptesicus serotinus, as well as an increase in groups of Nyctalus noctula, Pipistrellus kuhlii, Pipistrellus nathusii and Vespertilio murinus. In all seasons the least common and not numerous were Plecotus auritus, Myotis daubentonii, Nyctalus lasiopterus, Nyctalus leisleri, Hypsugo savii and Barbastella barbastellus.
Стан фауни кажанів українського Приазов'я в сучасних екологічних умовах
Keywords: Ukrainian Pryazovia; global warming; detector; bat; wind power plant; research; Українське Приазов'я; глобальне потепління; кажани; вітроелектростанція